Modified Switching Table-Based Direct Torque Control of Six-Phase Induction Motor Drive. Issue 11 (21st July 2019) - Shaikh Mo, Suhel A; Maurya, Rakesh; Gupta, Nitin
Abstract: This paper presents "Switching Table based Direct Torque Control" of Six-Phase Induction Motor (SPIM) Drive. The SPIM consists of two sets of stator windings spatially shifted by an angle of 30°. The extension of DTC technique of three-phase induction motor for a six-phase induction motor yields conventional DTC, in which one large voltage vector per sampling period is utilized. This technique suffers from large stator current harmonics of the order of 6 k ± 1 ( k = 1, 3, 5..). Initially, the conventional DTC technique has been implemented for comparison purpose. Further, its performance is improved by using two voltage vectors in each sampling period. In order to investigate the performance of ST-DTC based SPIM, a simulation study is carried out under different operating conditions. To validate the simulation results, a prototype model of six-phase induction motor rated for 1.5 kW, 200 V, 50 Hz is developed. Results obtained during simulation and experimentation show the effectiveness of modified ST-DTC technique in the reduction of stator current harmonics.